Master in Microsoft Power BI Desktop and Service - LLP, Learnsector; Kannan, Navya (Packt Publishing, 2021)
Enhance your skills with comprehensive knowledge on Power BI Desktop, Power BI Online, and the required hands-on experience to solve real-time industry-based Power BI projects About This Video Create, share, collaborate, and benefit from business information with purpose-built dashboards Create compelling reports and visualizations, derive real-time insights, and deploy it on demand Form relationships in your data model and learn data visualization best practices In Detail Power BI is a business intelligence tool by Microsoft that provides analytics services. It provides interactive dashboards and visualizations with self-service business intelligence capabilities, where end users can create reports and dashboards by themselves without having to depend on anyone else, as Power BI's artificial intelligence is there to help you out. Power BI provides cloud-based BI services, known as Power BI Services, along with a desktop-based interface called Power BI Desktop. It offers data modeling capabilities along with data preparation, data discovery, and interactive dashboards. In this course, you will gain an understanding of the concept and working of Power BI Desktop and Power BI online services. You'll start with learning how to connect Power BI to different data sources. Then you'll be able to transform your data using Power Query and create data models. After this, you'll also level up your data analysis skills using DAX and create calculated columns and measures. With the help of reports and visualization in Power BI, you'll be able to present your data in an efficient and interactive way. And lastly, you'll learn how to publish your reports and dashboards to the Power BI online service. By the end of this course, you'll be able to excel at your career as a business intelligence and data analyst professional.